Real-world evaluation of glycemic control among patients with type 2 diabetes mellitus treated with canagliflozin versus dipeptidyl peptidase-4 inhibitors. (2nd June 2016) - Thayer, Sarah; Chow, Wing; Korrer, Stephanie; Aguilar, Richard
Abstract: Objective To evaluate glycemic control among patients with type 2 diabetes mellitus (T2DM) treated with canagliflozin (CANA) vs. dipeptidyl peptidase-4 (DPP-4) inhibitors. Methods Using integrated claims and lab data from a US health plan of commercial and Medicare Advantage enrollees, this matched-control cohort study assessed adult T2DM patients receiving treatment with CANA or DPP-4 inhibitors (1 April 2013–31 December 2013). Cohorts were chosen hierarchically; the first pharmacy claim for CANA was identified as the index date; then the first pharmacy claim for a DPP-4 inhibitor was identified and index date set. Eligible patients had 6 months of continuous health plan enrollment before the index date (baseline) and 9 months after (follow-up) and no evidence of index drug in baseline. Patients were matched 1:1 using propensity score matching. Changes in glycated hemoglobin (HbA1c) and percentages of patients with HbA1c <8% and <7% during the follow-up were evaluated. Results The matched CANA and DPP-4 inhibitor cohorts (53.2% treated with sitagliptin) included 2766 patients each (mean age: 55.7 years). Among patients with baseline and follow-up HbA1c results, mean baseline HbA1c values were similar, 8.62% and 8.57% ( p = 0.615) for the CANA ( n = 729) and DPP-4 inhibitor ( n = 710) cohorts, respectively. Change in HbA1c was greater among patients in the CANA cohort than for those in the DPP-4 inhibitor cohort (−0.92% vs. −0.63%, p < 0.001), and also among the subset of patients with baseline HbA1c ≥7% (-1.07% [ n = 624] vs. −0.79% [ n = 603], p = 0.004). During follow-up, greater percentages of the CANA cohort relative to the DPP-4 inhibitor cohort achieved HbA1c of <8% (66.0% vs. 58.6%, p = 0.004) and <7% (35.4% vs. 29.9%, p = 0.022). Limitations This study was observational and residual confounding remains a possibility. Conclusions In this real-world study of patients with T2DM, CANA use was associated with greater HbA1c reduction and higher percentages of patients attaining HbA1c goals than those treated with DPP-4 inhibitors.